1991
DOI: 10.1037/0096-1523.17.3.807
|View full text |Cite
|
Sign up to set email alerts
|

Long-term perceptual memory for briefly exposed words as a function of awareness and attention.

Abstract: Two experiments investigated the possibility that perceptual memory for words is dependent on level of awareness of those words. In Experiment 1, subjects attempted to report briefly exposed words in a study phase and then identify words that faded into view in a test phase. Old words appeared in both the study and test phases, whereas new words appeared only in the test phase. Perceptual memory, indexed as the faster identification of old vs. new words, was observed only for words correctly reported in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
87
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(98 citation statements)
references
References 19 publications
(28 reference statements)
8
87
1
2
Order By: Relevance
“…Even if the "unattended" old words did receive some attentional processing, the lack of implicit memory for these words indicates that there is some necessary amount of attentional processing of a word that must be accomplished at encoding before it can influence performance on a later perceptual implicit memory test. The results confirm the observation of Hawley and Johnston (1991) that only when a stimulus undergoes sufficient attentional processing to support awareness of stimulus identity at encoding will there be evidence oflater perceptual implicit memory ofthe stimulus. In this way, even perceptual implicit memory appears to be similar to explicit memory (cf.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Even if the "unattended" old words did receive some attentional processing, the lack of implicit memory for these words indicates that there is some necessary amount of attentional processing of a word that must be accomplished at encoding before it can influence performance on a later perceptual implicit memory test. The results confirm the observation of Hawley and Johnston (1991) that only when a stimulus undergoes sufficient attentional processing to support awareness of stimulus identity at encoding will there be evidence oflater perceptual implicit memory ofthe stimulus. In this way, even perceptual implicit memory appears to be similar to explicit memory (cf.…”
Section: Discussionsupporting
confidence: 78%
“…Preattentive processing ofless data-limited, but still unattended, stimuli might support implicit perceptual memory. Eich (1984) and Hawley and Johnston (1991) employed focused attention paradigms, but their results provided different answers to the question of whether there is evidence for implicit perceptual memory for unattended words. Our goal in the present study was to further examine that question.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We estimated the perceptual memory for an item by the time taken by subjects to report the identity of that item. Researchers using the dot-clearing procedure have found that words previously attended to are identified faster than new words (e.g., Hawley & Johnston, 1991).…”
Section: Methodsmentioning
confidence: 99%